ARTIFICIAL INTELLIGENCE (AI) AND CHATGPT IN LEARNING: ASSESSING EFFECTIVENESS AND OVERCOMING CHALLENGES IN THE AGE OF INDUSTRY 4.0 - Gautama, Budhi Pamungkas; Indriana Agusti, Nila; Lazuardi, Dibias; Maman Fathurohman, Cecep (Pusat Pengembangan Sumber Daya Manusia Aparatur, 2024)
This research investigates the application of artificial intelligence (AI) in higher education, explicitly evaluating its effectiveness in fostering self-directed learning and self-assessment among university students. The primary objective is to assess how AI can enhance teaching-learning and promote greater learning independence. The study employed data analysis using the Rasch model and examined respondent demographics, with the sample comprising 82% male and 27% female students, predominantly aged 18-23 years. All participants were university students. Findings reveal that AI significantly decreased reliance on human guidance and facilitated increased student independence in learning. The Rasch model analysis highlighted the effectiveness of AI across various levels of learning difficulty, demonstrating its ability to adapt to individual student needs. In summary, AI integration in higher education boosts student independence and adapts to diverse learning challenges, underscoring its value in enhancing educational quality. Consequently, incorporating AI into higher education holds significant promise for advancing self-directed learning and improving academic outcomes.ABSTRAKPenelitian ini mengkaji penerapan kecerdasan buatan (AI) dalam pendidikan tinggi, dengan fokus pada efektivitasnya dalam mendukung pembelajaran mandiri dan penilaian diri di kalangan mahasiswa. Tujuan utama penelitian ini adalah untuk mengevaluasi bagaimana AI dapat meningkatkan proses pengajaran-pembelajaran dan mendorong kemandirian belajar di kalangan mahasiswa. Metode yang digunakan adalah analisis data menggunakan model Rasch dan evaluasi demografis responden, yang terdiri dari 82% mahasiswa laki-laki dan 27% mahasiswa perempuan, dengan sebagian besar berusia 18-23 tahun. Semua responden adalah mahasiswa. Hasil penelitian menunjukkan bahwa penggunaan AI secara signifikan mengurangi ketergantungan pada bimbingan manusia dan meningkatkan kemandirian mahasiswa dalam belajar. Analisis Model Rasch menunjukkan distribusi efektivitas penggunaan AI pada berbagai tingkat kesulitan belajar, mencerminkan kemampuan teknologi ini untuk beradaptasi dengan kebutuhan individu mahasiswa. Kesimpulannya, penerapan AI dalam pendidikan tinggi tidak hanya meningkatkan kemandirian mahasiswa tetapi juga dapat beradaptasi dengan berbagai tingkat kebutuhan dan kesulitan belajar, menjadikannya alat yang penting dalam meningkatkan kualitas pendidikan. Dengan demikian, integrasi AI dalam pendidikan tinggi memiliki potensi besar untuk memajukan pembelajaran mandiri dan efektivitas akademik.